2022
DOI: 10.3389/fneur.2022.870433
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Chronic Tinnitus Distress and Symptoms of Depression: A Systematic Review

Abstract: ObjectivesIn this systematic review, we aim to evaluate the evidence regarding the correlation between tinnitus distress and the severity of depressive symptoms in patients with chronic tinnitus. Also, the prevalence of clinically relevant depressive symptoms scores in patients with chronic tinnitus was evaluated.MethodsWe performed a systematic review in PubMed, EMBASE, and the Cochrane library in June 2021 using the terms “depression” and “tinnitus,” and their synonyms, following PRISMA guidelines. Studies w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 81 publications
0
6
0
Order By: Relevance
“…The BDI has shown to be a valid and reliable tool to evaluate depressive symptoms in patients with chronic pain [ 109 ]. It is also commonly used to assess depression in patients with tinnitus [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…The BDI has shown to be a valid and reliable tool to evaluate depressive symptoms in patients with chronic pain [ 109 ]. It is also commonly used to assess depression in patients with tinnitus [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…In a systematic review (47) in patients with chronic tinnitus, 7 out of 33 studies used HADS. According to the authors, although the data showed statistically positive correlation between tinnitus suffering and the severity of depression, symptomatic clinical depression was relatively rare in these individuals.…”
Section: Standard and Extend High-frequency Audiometry In Ssnhl E371mentioning
confidence: 99%
“…Additionally, non-auditory pathways play a critical role in the maintenance and affective response to tinnitus (Figure 2) [49]. Correspondingly, tinnitus is known to be co-morbid with depression and anxiety [50], and intracochlear-glucocorticoid-mediated glutamate release may be a link between psychological stressors and tinnitus [51]. The frontostriatal gating theory posits that the nucleus accumbens and ventromedial prefrontal cortex are important in the affective response to tinnitus [52].…”
Section: Etiology and Pathophysiologymentioning
confidence: 99%
“…morbid with depression and anxiety [50], and intracochlear-glucocorticoid-mediated glu tamate release may be a link between psychological stressors and tinnitus [51]. The fron tostriatal gating theory posits that the nucleus accumbens and ventromedial prefronta cortex are important in the affective response to tinnitus [52].…”
Section: Etiology and Pathophysiologymentioning
confidence: 99%